Assessing the public attitude toward low-income housing; (case study: Small- and medium-density cities of Iran) - Ramzanpour, Mehrnaz; Sharghi, Ali; Nourtaghani, Abdolmajid (Frontiers in Built Environment, 2022)
Low-income housing (LIH) is subject to stigma. This study aims to measure the public attitude toward it with respect to three main attitude components. The survey was carried out using an online questionnaire and non-resident sample. Using exploratory factor analysis, 11 factors were derived, including 7 cognitive factors (security, unit characteristics, spatial reputation, individual and environmental characteristics, physical attractiveness, and social interaction), 2 affective factors (feeling toward physical dimension and feeling toward residents), and 2 behavioral factors (social distance and situational behavior). Descriptive analysis may show that the attitude toward LIH is negative in Iran. Among them, physical factors related to the environment and building have the lowest scores. Thus, it is necessary to pay more attention to the reduction of LIH stigma with more interventions in the physical aspect. The regression test showed the highest correlation between the “social distance” and “feeling toward physical aspects,” whereas the highest correlation was observed between the “situational behavior” and “feeling toward residents”. It means outsiders are further influenced by physical factors when making distance-related decisions. When they are in a situation with exposure to these housings, their feelings toward the residents are more important and are reflected.